The Influence of Brand Image, Product Quality and Service Quality on Consumer Satisfaction with the Contemporary Drink Raja Boba in Tembung - Ayu Wulandari; Hendra Harmain; Ahmad Muhaisin B. Syarbaini (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2023)
The intense competition in the culinary world, especially in the world of contemporary boba drinks, means that entrepreneurs must be able to provide new and unique things, especially in the field of contemporary culinary drinks, to provide satisfaction to consumers. This research aims to partially determine the influence of brand image, product quality, and service quality on current consumer satisfaction with Raja Boba drinks in Tembung. The population of this research is Raja Boba consumers in Tembung. This research method is used, namely quantitative research using probability sampling techniques with a purposive sampling approach. Questionnaires will be distributed to Raja Boba customers in Tembung. The sample size is 40 respondents.  The data analysis methods used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests or T-tests. Partial hypothesis results show that brand image has no significant effect on Raja Boba customer satisfaction, product quality has no significant effect on Raja Boba customer satisfaction, and service quality has a significant effect on Raja Boba customer satisfaction. This research only focuses on brand image, product quality, and service quality on consumer satisfaction with the contemporary drink Raja Boba Di Tembung so the results cannot be generalized to all other luxury product categories. In the future product categories can be expanded to increase the generalizability of research models and research results.